Brachial and central hypertension in relation to coronary stenosis in patients with coronary angiography - Yu Chen; Ming‐Xuan Li; Ying Wang; Xian Jin; Liang Liu; Zhen‐Fa Zhou; Feng‐Hua Ding; Rui‐Yan Zhang; Yan Li; Cheng‐Xing Shen (The Journal of Clinical Hypertension, 2023)
Abstract The clinical significance of central beyond brachial blood pressure (BP) remains unclear. In patients who underwent coronary angiography, the authors explored whether elevated central BP would be associated with coronary arterial disease (CAD) irrespective of the status of brachial hypertension. From March 2021 to April 2022, 335 patients (mean age 64.9 years, 69.9% men) hospitalized for suspected CAD or unstable angina were screened in an ongoing trial. CAD was defined if a coronary stenosis of ≥50%. According to the presence of brachial (non‐invasive cuff systolic BP ≥140 mmHg or diastolic BP ≥90 mmHg) and central (invasive systolic BP ≥130 mmHg) hypertension, patients were cross‐classified as isolated brachial hypertension (n = 23), isolated central hypertension (n = 93), and concordant normotension (n = 100) or hypertension (n = 119). In continuous analyses, both brachial and central systolic BPs were significantly related to CAD with similar standardized odds ratios (OR, 1.47 and 1.45, p < .05). While categorical analyses showed that patients with isolated central hypertension or concordant hypertension had a significantly higher prevalence of CAD and the Gensini score than those with concordant normotension. Multivariate‐adjusted OR (95% confidence interval [CI]) for CAD was 2.24 (1.16 to 4.33, p = .009) for isolated central hypertension and 3.02 (1.58 to 5.78, p < .001) for concordant hypertension relative to concordant normotension. The corresponding OR (95% CI) of a high Gensini score was 2.40 (1.26–4.58) and 2.17 (1.19–3.96), respectively. In conclusion, regardless of the presence of brachial hypertension, elevated central BP was associated with the presence and severity of CAD, indicating that central hypertension is an important risk factor for coronary atherosclerosis.